Disaster risk reduction and sustainable development for small island developing states. Issue 1 (2nd January 2016) - Shultz, James M.; Cohen, Madeline A.; Hermosilla, Sabrina; Espinel, Zelde; McLean, Andrew
ABSTRACT: In contrast to continental nations, the world's 52 small island developing states (SIDS) are recognized as a collective of countries that experience disproportionate challenges for sustainable development related to their geography, small size, and physical isolation. These same states also face elevated risks for disaster incidence and consequences particularly in the realms of climate change, sea level rise, natural disasters (tropical cyclones, earthquakes, tsunamis, volcanoes), and marine hazardous materials spills. Cyclone Winston's direct impact on Fiji in 2016 and Cyclone Pam's landfall over Vanuatu in 2015 provide case examples illustrating the special vulnerabilities of the SIDS.